Odpowiedzi

2010-03-25T20:37:48+01:00
2010-03-25T20:38:14+01:00
A) -5t + t - 6 - 7t + 8t + 2 + 2t dla t = -3,2
5t-4 5razy(-3,2)-4
-16-4=-20
b)-7x + 6y +3x - 2y + x - 3y dla x = -⅔ i y= ₇⁴ (cztery siódme)
-3x-y -3razy-⅔-(cztery siódme)
2-(cztery siódme)=1(trzy siódme)
Najlepsza Odpowiedź!
2010-03-25T20:41:32+01:00
A) -5t + t - 6 - 7t + 8t + 2 + 2t=-1t-4-zredagowane wyrazy

=-1*(-3,2)-4=3,2-4=-0,8 -obliczonko :p


b)-7x + 6y +3x - 2y + x - 3y= -3x+y-zredagowane wyrazy podobne

=-3*(-dwie trzecie)+(cztery siódme)=2+ (cztery siódme)
=2 i(cztery siódme)

licze na punkty :) i że pomogłem